Managing asymmetric resource dependence and environmental risk in relationships by real options - Ellen Roemer (Management Revue, 2004)
All economic action is embedded in social contexts (Granovetter 1985). However, contingent work practices make work relations more episodic, transient and marketlike. They produce dislocated and time-space spanning social contexts and, therefore, contribute to what Giddens (1990) has called the process of disembedding. The aim of the paper is to relate contingent work practices to a wider societal context by looking at how these disembedded practices become reembedded in local contexts of interaction. For situations in which means-end calculations are the dominant focus of social relations and in which social interactions are, for the most part, consciously reflected as resource exchange relations, the term economic reembedding is suggested. But - illustrated by Bourdieu's notion of social capital - the paper also explores limits to an economization of social relations in general and of work practices in particular. In conclusion, some implications for firms' utilization, management, and reproduction of human resources are discussed that follow on from the embeddedness perspective on contingent work developed in the paper.
Keywords: 650; resource dependence; relationships; risk; real options; Lieferanten-Kunden-Beziehung; Ressourcenorientierter Ansatz; Ressourcenabhängigkeits-Ansatz